PROJECTION METHOD IN THE INTEGRATION OF DESIGN ELEMENTS AND ENGINEERING GRAPHICS AND DESIGN SCIENCES - Haqberdiyev, B.R. (SCIENCE and SOCIETY, 2022)
The given article deals witn creating design methods via canpounding graphic engineering and design tools. Investigated technique is effective for students of speciality fine art and engineer graphics.